Rice Yield and Nitrogen Use Efficiency With System of Rice Intensification and Conventional Management Practices in Mkindo Irrigation Scheme, Tanzania - Mboyerwa, Primitiva Andrea; Kibret, Kibebew; Mtakwa, Peter; Aschalew, Abebe (Frontiers in Sustainable Food Systems, 2022)
Aim This study investigated the impacts of system of rice intensification (SRI) and conventional management practice (CP) on rice growth, grain yield, and nitrogen use efficiency by nitrogen application. Methods Field experiments were conducted in wet and dry seasons; each season, the experiment was set in a split-plot randomized complete block design in triplicate with crop management practices in main plots and nitrogen levels in subplots. Results The average grain yield by SRI was 7.1 and 6.7 t ha−1, while by CP it was 6.1 and 4.4 t ha−1in the wet and dry seasons, respectively. The grain yield of the SRI practice was significantly (p < 0.05) greater than that of the conventional practice (CP) at all levels of nitrogen application. The average yield under the treatment interaction of SRI and nitrogen levels were increased by 13.1% in the wet season and 35.8 % in the dry season. Roots of SRI plants had significantly (p < 0.05) greater fresh weight, length, and volume as indicated by increased root dry weight per hill. SRI improved crop growth, effective tillers, filled grains per panicle, grain filling rate, panicle weight, spikelet per panicle, straw yield, and 1,000-grain weight. Nitrogen application rate had a significant effect (p < 0.05) on agronomic nitrogen use efficiency (ANUE). As the N application rate was increased beyond 90 kg N ha−1, the ANUE and partial factor productivity (PFP) under both SRI and CP were significantly decreased in both seasons. Conclusion Overall, the SRI production system with 60 kg N ha−1 improved rice growth, yield, and nitrogen use efficiency compared to the CP.